Does a Platelet Transfusion Independently Affect Bleeding and Adverse Outcomes in Cardiac Surgery?. (March 2017) - van Hout, Fabienne M. A.; Hogervorst, Esther K.; Rosseel, Peter M. J.; van der Bom, Johanna G.; Bentala, Mohamed; van Dorp, Eveline L. A.; van Geloven, Nan; Brand, Anneke; van der Meer, Nardo J. M.; van de Watering, Leo M. G.
Abstract : Background: Conflicting results have been reported concerning the effect of platelet transfusion on several outcomes. The aim of this study was to assess the independent effect of a single early intraoperative platelet transfusion on bleeding and adverse outcomes in cardiac surgery patients. Methods: For this observational study, 23, 860 cardiac surgery patients were analyzed. Patients who received one early (shortly after cardiopulmonary bypass while still in the operating room) platelet transfusion, and no other transfusions, were defined as the intervention group. By matching the intervention group 1:3 to patients who received no early transfusion with most comparable propensity scores, the reference group was identified. Results: The intervention group comprised 169 patients and the reference group 507. No difference between the groups was observed concerning reinterventions, thromboembolic complications, infections, organ failure, and mortality. However, patients in the intervention group experienced less blood loss and required vasoactive medication 139 of 169 (82%) versus 370 of 507 (74%; odds ratio, 1.65; 95% CI, 1.05 to 2.58), prolonged mechanical ventilation 92 of 169 (54%) versus 226 of 507 (45%; odds ratio, 1.47; 94% CI, 1.03 to 2.11), prolonged intensive care 95 of 169 (56%) versus 240 of 507 (46%; odds ratio, 1.49; 95% CI, 1.04 to 2.12), erythrocytes 75 of 169 (44%) versus 145 of 507 (34%; odds ratio, 1.55; 95% CI, 1.08 to 2.23), plasma 29 of 169 (17%) versus 23 of 507 (7.3%; odds ratio, 2.63; 95% CI, 1.50–4.63), and platelets 72 of 169 (43%) versus 25 of 507 (4.3%; odds ratio, 16.4; 95% CI, 9.3–28.9) more often compared to the reference group. Conclusions: In this retrospective analysis, cardiac surgery patients receiving platelet transfusion in the operating room experienced less blood loss and more often required vasoactive medication, prolonged ventilation, prolonged intensive care, and blood products postoperatively. However, early platelet transfusion was not associated with reinterventions, thromboembolic complications, infections, organ failure, or mortality. Abstract : In a retrospective, observational study with propensity matching of more than 23, 000 patients, the authors show that platelet transfusions in cardiac surgery were associated with less blood loss but increases in some other perioperative factors including increased requirements for vasoactive medications, supportive ventilation, and prolonged intensive care. No association between platelet transfusion and surgical reinterventions, thrombotic complications, infections, organ failure, or mortality was found.Supplemental Digital Content is available in the text.